Transportation Management in Universitas Indonesia - Kiswanto, Gandjar; Hanzen, Denni; Safitri, Faradilla; Febrianty, Farizha (Universitas Diponegoro, 2021)
Transportation management is one of the supports for a green and healthy campus. The increasing number of campus population has an impact on the number of vehicles entering the campus environment. So that in order to reduce the number of incoming vehicles, transportation management in the Universitas Indonesia is needed. In addition to regulating the transportation system on campus, transportation management also regulates the prohibition of the UI Civitas Academica from bringing private vehicles into the campus environment. To limit the vehicles that enter the campus environment, UI takes strategic steps such as making policies, building support facilities and planning that have been prepared and will be explained in this paper. to reduce and limit vehicles in the campus environment One of the steps taken by the Universitas Indonesia is to provide Zero Emissions Vehicle (ZEV) transportation such as buses, bicylce, and scooters as a means of transportation that can be used for free by the UI Civitas Academica. To reduce and restrict private vehicles, UI is building a Highway Distribution to facilitate pedestrians, building a BORR (Bikers Outer Ring Road) lane for motorbikes, implementing a gate parking system at every entrance to the UI campus, In addition, UI also enforces various policies such as reducing the parking area, and prohibiting semester 1 and 2 students from bringing private vehicles into the campus environment, this is done by UI to reduce vehicles entering the UI campus